Risk factors, complications and biomarkers associated with acute kidney injury after craniotomy: a comprehensive mini‐review - Davood Dalil; Joben Kianparsa; Mahdi Isakhani; Mahdieh Ostadzadeh; Fatemeh Ravand (Acute Medicine & Surgery)
Abstract Acute kidney injury (AKI) is a devastating medical condition that occurs mostly in hospitalized patients after a serious illness or major surgery and imposes a great health and financial burden on patients. Craniotomy is one of the major surgeries in which people who undergo this operation experience critical clinical conditions. Systemic inflammation, hemodynamic variation, and pharmacological agents administered during and after craniotomy can lead to the development of AKI and a poor prognosis. Moreover, AKI itself could cause other significant complications and increase the mortality rate in patients who undergo craniotomy. Determining the pre‐, peri‐, and postoperative risk factors associated with AKI after craniotomy is important for its prevention. Efficient care of patients after craniotomy and effective treatment approaches should be implemented to maintain normal metabolism, enhance nerve function recovery, and control inflammation. Novel biomarkers have been recognized as reliable indicators for the diagnosis and prognosis of AKI after brain surgery. This study aimed to summarize the most relevant literature regarding the risk factors, postoperative complications, and mortality associated with AKI after craniotomy. Moreover, we reviewed the approaches to postoperative care, followed by an overview of the significant diagnostic or prognostic biomarkers of AKI following craniotomy to provide a basis for preventing and decreasing AKI.